The Tragic/Comic Calisto: Obsessed and Insecure - Connie L. Scarborough (Celestinesca, 2021)
Calisto emerges from the pages of the Tragicomedia de Calisto y Melibea as a more complex character than he initially appears. Rather than a mere stereotype of the courtly lover the contradictions and inconsistencies he manifests reveal his own insecurities. While blindly pursuing his sexual passion for Melibea he fails to manage well his own household and constantly seeks the approval and help of his servants and Celestina. He even fails as the long-suffering lover when he continuously shows himself to be impatient and irritable to all around him. Calisto is the king of rhetorical excess and but shows a single lack of confidence in Celestina even though he handsomely rewards. He misuses religious belief by praying for Melibea's affections and completely misreads the motivations and character of his servants. When he does possess Melibea physically, he treats her harshly and his rhetoric is crude in contrast to his courtly speeches he offers when not in her presence. Calisto is both a tragic and comic figure and readers of the Tragicomedia witness the cruel consequences of blind obsession while also laughing at the fool in love.